L’idée d’« individu pur » dans la pensée de Simondon - Ludovic Duhem (Appareil)
Gilbert Simondon’s ontologic project is to consider the individual through individuation in all the reality domains: physical, biological, and psycho-social or “transindividual”. To Simondon, it is precisely a question of reversring the ontologic privilege attached to being on becoming, to result on operation, to individual on individuation by the means of metaphysics, thus making it the condition of complete knowledge of reality. Now, the « individu pur » idea, as it is developed in only two texts of L’individuation à la lumière des notions de forme et d’information, in the biological and psycho-technical domains, stand in the way of maintaining of this reversal by replacing a kind of substancialism. This difficulty which pushes Simondon to his own limit will be the opportunity of examine two individuation cases and, through them, the coherence and the implications of his thought.